A study on the constraints of implementing Information and Communication Technology (ICT) in Malaysian Construction Industry. Issue 1 (November 2019) - Lew, Y L; Toh, T C; Lim, K L; Yan, F Y Y; Yow, L P
Abstract: Information and Communication Technology (ICT) refers to a combination of hardware, software and communication facilities. Often, ICT is introduced to equip construction stakeholders with information and analytical tools for a better control throughout the entire construction delivery process. The aim of this study is to investigate the issues relating to implementation of ICT in Malaysian construction industry with the objectives of: (i) to identify the benefits of adopting ICT in construction industry; (ii) to determine the constraints of implementing ICT in construction industry; and (iii) to identify the methods to encourage construction industry in adopting ICT. A questionnaire survey was conducted in Johor and Klang Valley of Malaysia, a total of 70 completed questionnaires were collected from contractors and quantity surveying consultation firm. Based on the analysis conducted, the top three benefits of adopting ICT in Malaysian construction industry ranked by the respondents are improvement on accuracy of measurement works, minimization on usage of paper by digitalization and allowed rapid sharing of information among project team. The barriers in implementing ICT in Malaysian construction industry identified included unaffordable initial capital and long term investment required, difficulties encountered to recruit capable and trustworthy in-house IT specialist, and security issues on confidential issues. Training and vendor's efforts to improve their software have been agreed as the most achievable and practical methods to encourage ICT uptake. This study had explore the implementation and acceptance level of ICT in Malaysian construction industry. The views from both contractor and quantity surveying consultation firm were revealed. The findings from this study could be used as the baseline for future development of ICT in the local construction industry.